Waterbirds as ecosystem flagships of Eurasian inland saline waters: Dual control indicators of trophic structure - Emil Boros; Zsolt Végvári; Anita Kiss; Péter Dobosy; Zarina Inelova; Yelena Zaparina; Andrey Gavrilov; Lajos Vörös (Ecological Indicators)
The main objective of the study is to compare the trophic systems of intermittent and permanent shallow standing waters with wide salinity gradients (1–500 < g/L) and various salt compositions on Eurasian large scales. We analysed the nutrient-phytoplankton-zooplankton-fish-bird trophic network in the intermittent and permanent as well as non-alkaline saline and alkaline soda waters. The algal biomass of alkaline soda waters were significantly larger due to the improved phosphorus supply than in saline waters. The biomass of zooplankton (Rotifera, Crustacea) increased up to the threshold level (50 g/L) of the salinity, as salt-tolerant taxa can reproduce en masse without competition in the hypertrophic range. The zooplankton biomass is primarily regulated by desiccation as a result of the lack of fish top-down control. The investigated waters are net heterotrophic systems as the amount of zooplankton biomass exceeds the quantities expected from the phytoplankton biomass. Our investigation demonstrated that the nutrient import by waterbird faeces (guanotrophication) provides a significant bottom-up control in these systems, which may lead to net heterotrophy. The top-down control of zooplankton by fish can be partly replaced by filter-feeding waterbirds in intermittent waters. As intermittent waters are dominated by the waterbird–heterotrophic microorganisms–phytoplankton–zooplankton–waterbird food web, these ecosystems are dually controlled by waterbirds as shortcut agents in the trophic chain. Therefore, waterbirds can be regarded as ecosystem flagship indicator taxa of these migratory hotspots of flyways. Our study presents a novel trophic model that integrates desiccation, salinity, chemistry, nutrient cycle, and multiple effects of waterbirds on these ecosystems.